2008
DOI: 10.1038/ncb1752
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial adherens junctions control tight junctions by VE-cadherin-mediated upregulation of claudin-5

Abstract: Intercellular junctions mediate adhesion and communication between adjoining cells. Although formed by different molecules, tight junctions (TJs) and adherens junctions (AJs) are functionally and structurally linked, but the signalling pathways behind this interaction are unknown. Here we describe a cell-specific mechanism of crosstalk between these two types of structure. We show that endothelial VE-cadherin at AJs upregulates the gene encoding the TJ adhesive protein claudin-5. This effect requires the relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
534
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(590 citation statements)
references
References 50 publications
34
534
3
3
Order By: Relevance
“…VE-cadherin upregulates claudin-5 expression by suppressing the nuclear localization of the FoxO1-b-catenin complex that inhibits claudin-5 expression (Taddei et al, 2008); their SphK2-dependent, co-upregulation by HPC before stroke that we observed may help establish the BBBprotective phenotype we documented in HPC-treated mice.…”
Section: Discussionsupporting
confidence: 52%
“…VE-cadherin upregulates claudin-5 expression by suppressing the nuclear localization of the FoxO1-b-catenin complex that inhibits claudin-5 expression (Taddei et al, 2008); their SphK2-dependent, co-upregulation by HPC before stroke that we observed may help establish the BBBprotective phenotype we documented in HPC-treated mice.…”
Section: Discussionsupporting
confidence: 52%
“…Both p120 and b-catenin transcription factors that are released from adhesion complexes by permeability factors such as thrombin are known to translocate to the nucleus and activate target genes 9 . VE-cadherin clustering phosphorylates and suppresses FOXO1 via the PI3K-Akt pathway, leading to the upregulation of claudin-5 expression 8 . Here, we added another transcriptional regulatory mechanism that is triggered by VE-cadherin:…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that VE-cadherin is involved in the transcriptional regulation of genes, including claudin-5 (ref. 8). VE-cadherin-mediated cellcell interaction activates the PI-3/Akt pathway, leading to phosphorylation and inactivation of FoxO1 transcriptional repressor, which results in upregulation of claudin-5 (ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that loss of VE-cadherin adhesive function is a key event in endothelial junction remodeling and loss of barrier integrity (Dejana, 2004;Gavard and Gutkind, 2006;Taddei et al, 2008). To this regard, we first investigated the architecture of cell-cell junctions in vGPCR-expressing endothelial cells by electron microscopy.…”
Section: Ve-cadherin-dependent Cell-cell Contacts Are Disorganized Inmentioning
confidence: 99%